Soil and groundwater remediation : fundamentals, practices and sustainability - Zhang, Chunlong, 1964- (John Wiley & Sons, Inc., 2020)
"This textbook provides a comprehensive overview on soil and groundwater remediation in the context of principles, practices and sustainability. The book is to be used as a college textbook targeted primarily for students in environmental science and engineering as well as a reference book for environmental professionals who have not received comprehensive training of the subject but are involved in various stages of site assessment and environmental remediation. The book starts with an introductory chapter in describing the importance of groundwater resource, groundwater quality, contaminant sources and types, and the scope of soil and groundwater remediation. It then provides remediation basics such as subsurface chemical behaviors, soil and groundwater hydrology and characterization, regulations, cost analysis, and risk assessment. This is followed by various conventional and innovative remediation technologies, including pump-and-treat, soil vapor extraction, bioremediation, incineration, thermally enhanced techniques, soil washing/flushing, and permeable reactive barriers. The book ends with a chapter dedicated to the modeling of groundwater flow and contaminant transport in saturated and unsaturated zones"--